Method for testing hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hull

Through the method of embossing hull detection, the problem of hydrogen embrittlement testing time of hydrogen embrittlement insensitive materials in the prior art is solved, and the sensitivity to hydrogen embrittlement detection is improved and the test cycle is shortened.

CN119738260APending Publication Date: 2025-04-01JIANGSU LONGCHENG PREC FORGING CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935519.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, hydrogen embrittlement testing of hydrogen embrittlement insensitive materials usually uses plate-like samples for slow stretching, and the test time is long and insensitive to hydrogen embrittlement.

Method used

The hull test method is used to select hydrogen embrittlement insensitive material samples, and electrolyte hydrogen or hydrogen-free hydrogen is not charged. The cup-protrusion test tool is used to perform cup-protrusion test, and the height of the sample protrusion is measured as a measurement indicator for hydrogen embrittlement.

Benefits of technology

The sensitivity of hydrogen embrittlement detection of hydrogen embrittlement insensitive materials is improved, which can better reflect the damage caused to the material after hydrogen infiltration, and the test cycle is short.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119738260A_ABST
    Figure CN119738260A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen embrittlement performance detection and sample processing of hydrogen embrittlement insensitive materials, and discloses a method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls. The method comprises the following steps: first, selecting hydrogen embrittlement insensitive material samples, wherein the number of the samples is 3-6; second, manually polishing both sides of each sample with sandpaper; third, electrolyzing and hydrogenating half of the polished samples, and not charging the remaining half of the samples; fourth, installing the samples on the test tooling by using an Erickson cupping test tooling and requirements; and fifth, performing a cupping test on the samples according to the requirements of standard GB / T 4156-2007, until the pressure head stops moving and is unloaded when the pressure is reduced, and then taking out the samples. The invention provides a new shape and size of hydrogen embrittlement insensitive material samples, and provides a basis for the reliability of measurement data. By using the method of pressing convex hulls for testing, the detection sensitivity of hydrogen embrittlement of hydrogen embrittlement insensitive materials can be improved, and the damage to the materials caused by hydrogen penetration can be better reflected, and the test cycle is short.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen embrittlement performance detection and sample processing of hydrogen embrittlement insensitive materials, in particular to a method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls. Background Art

[0002] In the context of the popularization of new energy, the number of hydrogen embrittlement insensitive materials used in hydrogen storage tanks and pipeline components is gradually increasing, and the problem of hydrogen embrittlement detection of such materials is becoming more urgent. At present, the research on the hydrogen embrittlement performance of hydrogen embrittlement insensitive materials is not in-depth, and the testing methods are relatively limited. The current hydrogen embrittlement detection mainly involves slow tensile testing to observe changes in plasticity indicators, that is, elongation or cross-sectional shrinkage. The process is generally to first make the material into a plate-shaped tensile specimen, then perform hydrogen permeation, and then perform a slow tensile test after hydrogen permeation to obtain comparative data on plasticity indicators to measure the impact of hydrogen embrittlement.

[0003] At present, the hydrogen embrittlement test of hydrogen embrittlement insensitive materials is usually carried out by slow stretching of plate specimens. The test time often takes more than ten hours or even longer. In addition, the slow stretching of plate specimens is not very sensitive to hydrogen embrittlement, because when this kind of specimen is stretched, only the tensile direction has a large tensile stress, while the tensile stresses in the other two directions are very small. This stress state makes the specimen have better plasticity and cannot sensitively display the brittleness induced by hydrogen embrittlement. Therefore, a method of detecting the hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hull is proposed. Summary of the invention

[0004] The object of the present invention is to provide a method for detecting hydrogen embrittlement performance of hydrogen embrittlement-insensitive materials by pressing convex humps, so as to solve the problem mentioned in the above background technology that the hydrogen embrittlement test of hydrogen embrittlement-insensitive materials is usually carried out by slow stretching of plate-shaped specimens, and the test time often takes more than ten hours or even longer, and the slow stretching of plate-shaped specimens is not very sensitive to hydrogen embrittlement, because when such a specimen is stretched, only the tensile direction has a large tensile stress, while the tensile stresses in the other two directions are very small. This stress state makes the specimen have better plasticity and cannot sensitively display the brittleness induced by hydrogen embrittlement.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls, comprising the following steps:

[0006] Step 1: Select 3-6 samples of hydrogen embrittlement insensitive materials;

[0007] Step 2: Manually polish both sides of each sample with sandpaper;

[0008] Step 3: electrolytically charge half of the ground sample with hydrogen, and do not charge the remaining half of the sample with hydrogen;

[0009] Step 4: Use the Erickson cupping test fixture and requirements to install the sample on the test fixture;

[0010] Step 5: According to the requirements of GB / T 4156-2007, perform a cupping test on the sample until the pressure head stops moving and unloads when the pressure decreases, and then take out the sample;

[0011] Step 6: Measure the height of the protrusion of the sample, and use the protrusion height as a measure of hydrogen embrittlement;

[0012] Step 7: Repeat the measurement for each sample for multiple times and take the average value;

[0013] Step 8: Compare the average height values ​​to obtain the comparison results of the materials charged with hydrogen and those not charged with hydrogen.

[0014] Preferably, in step 1, the hydrogen embrittlement insensitive material sample selected may be one of 6082 aluminum alloy, 304 austenitic stainless steel, and C10100 pure copper.

[0015] Preferably, in step 1, the diameter of the sample is selected to be ≥ 75 mm.

[0016] Preferably, in step 1, the thickness of the sample is selected to be 2 mm.

[0017] Preferably, in the above step 2, after the sample is polished, machining marks are completely removed to ensure that the thickness is accurate to 0.01 mm.

[0018] Preferably, in step five, the pressure head speed is 10 mm / min.

[0019] Preferably, in step five, the diameter of the convex bulge after the sample is pressed is ≤24 mm.

[0020] Preferably, in step six, the measurement accuracy of the protrusion height needs to reach 0.1 mm.

[0021] Preferably, the ratio of the diameter of the bulge after the sample is convexly pressed to the diameter of the sample is ≤0.35.

[0022] Preferably, in step one, the number of samples is 6; in step seven, each sample is measured three times and the average value is taken.

[0023] Compared with the prior art, the present invention adopts the above technical scheme and has the following technical effects: the present invention provides a new shape and size of a hydrogen embrittlement insensitive material sample, providing a basis for the reliability of measurement data; by adopting the convex hull compression method for testing, the detection sensitivity of hydrogen embrittlement of hydrogen embrittlement insensitive materials can be improved, and the damage to the material caused by hydrogen penetration can be better reflected, and the test cycle is short. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is a schematic diagram of the convex hull pressing principle of the present invention;

[0026] Figure 2 This is a schematic diagram of the X-direction stress of the convex hull of the present invention;

[0027] Figure 3 It is a schematic diagram of the Y-direction stress of the convex hull of the present invention;

[0028] Figure 4 It is a schematic diagram of the Z-direction stress of the convex bulge of the present invention;

[0029] Figure 5 This is a schematic diagram of the uniaxial tensile X-direction stress of the present invention;

[0030] Figure 6 This is a schematic diagram of the Y-direction stress of uniaxial tension of the present invention;

[0031] Figure 7 This is a schematic diagram of the uniaxial tensile Z-direction stress of the present invention;

[0032] Figure 8 This is a schematic diagram of equivalent stress of the convex hull of the present invention;

[0033] Fig. 9 It is a schematic diagram of the uniaxial tensile equivalent stress of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the conditions under which this application can be implemented. Therefore, they have no substantive technical significance. Any structural modification, change in proportional relationship or adjustment of size should still fall within the scope of the technical content disclosed in this application without affecting the effects and purposes that can be achieved by this application.

[0036] Example 1

[0037] See also Figure 1-9 The present invention provides a technical solution: a method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls, comprising the following steps:

[0038] Step 1: Select 6082 aluminum alloy samples, the number of samples is 6, the diameter of the selected samples is 75 mm, and the thickness of the selected samples is 2 mm;

[0039] Step 2: Manually polish both sides of each sample with 500# sandpaper. After polishing, completely remove the machining marks and ensure that the thickness is accurate to 0.01mm.

[0040] Step 3: Electrolytically charge 3 ground samples with hydrogen, and do not charge the remaining 3 samples with hydrogen;

[0041] Step 4: Use the Erickson cupping test fixture and requirements to install the sample on the test fixture;

[0042] Step 5. According to the requirements of GB / T 4156-2007, the sample is subjected to a cupping test until the pressure is reduced and the pressure head stops moving and is unloaded, and the sample is taken out. The pressure head speed is 10 mm / min, and the diameter of the convex bulge of the sample is 24 mm.

[0043] Step 6: Measure the height of the protrusion of the sample and use the protrusion height as a measure of hydrogen embrittlement. The measurement accuracy of the protrusion height must reach 0.1mm;

[0044] Step 7: Repeat the measurement three times for each sample and take the average value;

[0045] Step 8: Compare the average height values ​​to obtain the comparison results of the materials charged with hydrogen and those not charged with hydrogen.

[0046] The ratio of the convex bulge diameter to the diameter of the sample after the sample is pressed into a convex bulge is 0.32.

[0047] Example 2

[0048] The difference from Example 1 is that the method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls comprises the following steps:

[0049] Step 1: Select 304 austenitic stainless steel samples, the number of samples is 6, the diameter of the selected samples is 75 mm, and the thickness of the selected samples is 2 mm;

[0050] Step 2: Manually polish both sides of each sample with 500# sandpaper. After polishing, completely remove the machining marks and ensure that the thickness is accurate to 0.01mm.

[0051] Step 3: Electrolytically charge 3 ground samples with hydrogen, and do not charge the remaining 3 samples with hydrogen;

[0052] Step 4: Use the Erickson cupping test fixture and requirements to install the sample on the test fixture;

[0053] Step 5. According to the requirements of GB / T 4156-2007, the sample is subjected to a cupping test until the pressure is reduced and the pressure head stops moving and is unloaded, and the sample is taken out. The pressure head speed is 10 mm / min, and the diameter of the convex bulge of the sample is 24 mm.

[0054] Step 6: Measure the height of the protrusion of the sample and use the protrusion height as a measure of hydrogen embrittlement. The measurement accuracy of the protrusion height must reach 0.1mm;

[0055] Step 7: Repeat the measurement three times for each sample and take the average value;

[0056] Step 8: Compare the average height values ​​to obtain the comparison results of the materials charged with hydrogen and those not charged with hydrogen.

[0057] The ratio of the convex bulge diameter to the diameter of the sample after the sample is pressed into a convex bulge is 0.32.

[0058] Example 3

[0059] The difference from Embodiments 1 and 2 is that the method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls comprises the following steps:

[0060] Step 1: Select 6 C10100 pure copper samples, the diameter of the sample is 75 mm, and the thickness of the sample is 2 mm;

[0061] Step 2: Manually polish both sides of each sample with 500# sandpaper. After polishing, completely remove the machining marks and ensure that the thickness is accurate to 0.01mm.

[0062] Step 3: Electrolytically charge 3 ground samples with hydrogen, and do not charge the remaining 3 samples with hydrogen;

[0063] Step 4: Use the Erickson cupping test fixture and requirements to install the sample on the test fixture;

[0064] Step 5. According to the requirements of GB / T 4156-2007, the sample is subjected to a cupping test until the pressure is reduced and the pressure head stops moving and is unloaded, and the sample is taken out. The pressure head speed is 10 mm / min, and the diameter of the convex bulge of the sample is 24 mm.

[0065] Step 6: Measure the height of the protrusion of the sample and use the protrusion height as a measure of hydrogen embrittlement. The measurement accuracy of the protrusion height must reach 0.1mm;

[0066] Step 7: Repeat the measurement three times for each sample and take the average value;

[0067] Step 8: Compare the average height values ​​to obtain the comparison results of the materials charged with hydrogen and those not charged with hydrogen.

[0068] The ratio of the convex bulge diameter to the diameter of the sample after the sample is pressed into a convex bulge is 0.32.

[0069] By providing a new shape and size of the sample of hydrogen embrittlement insensitive material, a basis is provided for the reliability of the measurement data; by using the convex hull method for testing, the detection sensitivity of hydrogen embrittlement of hydrogen embrittlement insensitive materials can be improved, better reflecting the damage caused to the material after hydrogen penetration, and the test cycle is short.

[0070] By using a large-area flat plate specimen, a convex hull test is performed at the center of the flat plate. The test principle is shown in Figure 1 After the sample is installed on the testing machine, the convex bulge test is carried out. When a crack appears on the top of the bulge, the loading is stopped, the sample is removed and the bulge height is measured. The size of hydrogen embrittlement is determined according to the height. In order to facilitate operation, the Ericsson testing machine and experimental fixture are directly used, and the pressure head speed is a high speed of 10mm / min.

[0071] Since the ratio of the convex hull diameter to the billet diameter is less than 0.35, during the convex hull pressing process, the deformation of the sample is concentrated in the convex hull area, and the plane does not participate in the deformation, resulting in severe deformation in the convex hull area, and the tensile stress reaches the maximum here. Through simulation research on 6082 aluminum alloy materials, it can be seen that when pressing the convex hull, the tensile stress distribution in the three directions of X, Y, and Z is as follows: Figure 2 , 3 As shown in Figure 4, there are large tensile stresses in the X and Y directions in the top area of ​​the convex hull, and the tensile stresses are almost equal, with the maximum values ​​of about 180 and 188 MPa respectively. The compressive stress in the Z direction is very small and can be ignored. The three-dimensional stress combination is that the tensile stress in two directions is very high, and the other direction is very small. The equivalent stress reaches 192 MPa.

[0072] The stress state of the plate specimen during uniaxial tension is shown in Figure 5 , 6 and 7, where there is a large tensile stress in the Y direction, that is, the tensile direction, reaching 164MPa, and the tensile stress in the other two directions is very small and negligible. The three-dimensional stress combination is that the tensile stress in one direction is very high, and the other two directions are very small, and the equivalent stress is 164MPa. Compared with plate-like stretching, the equivalent stress of the convex hull is increased by about 17%, as shown in the comparison. Figure 8 and 9 .

[0073] In the prior art, under the triaxial stress state, the more tensile stresses there are and the larger their values ​​are, the worse the plasticity of the metal is, because tensile stress can easily separate the slip planes and easily cause stress concentration at the defects inside the material, resulting in damage. Therefore, when hydrogen embrittlement occurs, the convex hull test makes the plasticity of the material even lower. Under the action of high tensile stress in two directions, the defects caused by hydrogen elements inside the material are more likely to experience stress concentration and then damage than under uniaxial tensile stress, and are more likely to show the influence of hydrogen embrittlement.

[0074] The following is a simulation study of 6082 aluminum alloy, 304 austenitic stainless steel and C10100 pure copper, comparing the data of the convex hull test and the unidirectional tensile test, as follows:

[0075]

[0076] It will be appreciated by those skilled in the art that the features described in the various embodiments and / or claims of the present invention may be combined and / or combined in various ways, even if such combinations and / or combinations are not explicitly described in the present invention. In particular, the features described in the various embodiments and / or claims of the present invention may be combined and / or combined in various ways without departing from the spirit and teachings of the present invention. All of these combinations and / or combinations fall within the scope of the present invention.

Claims

1. A method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls, characterized in that: The following steps are involved: Step 1: Select 3-6 samples of hydrogen embrittlement insensitive materials; Step 2: Manually polish both sides of each sample with sandpaper; Step 3: electrolytically charge half of the ground sample with hydrogen, and do not charge the remaining half of the sample with hydrogen; Step 4: Use the Erickson cupping test fixture and requirements to install the sample on the test fixture; Step 5: According to the requirements of GB / T 4156-2007, perform a cupping test on the sample until the pressure head stops moving and unloads when the pressure decreases, and then take out the sample; Step 6: Measure the height of the protrusion of the sample, and use the protrusion height as a measure of hydrogen embrittlement; Step 7: Repeat the measurement for each sample for multiple times and take the average value; Step 8: Compare the average height values ​​to obtain the comparison results of the materials charged with hydrogen and those not charged with hydrogen.

2. The method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls according to claim 1, characterized in that: In step 1, the selected hydrogen embrittlement insensitive material sample can be one of 6082 aluminum alloy, 304 austenitic stainless steel, and C10100 pure copper.

3. The method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex humps according to claim 1, characterized in that: In step 1, select a sample with a diameter ≥ 75 mm.

4. The method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex humps according to claim 1, characterized in that: In step 1, the thickness of the sample is selected to be 2 mm.

5. The method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls according to claim 1, characterized in that: In step 2, after the sample is polished, the machining marks must be completely removed to ensure that the thickness is accurate to 0.01mm.

6. The method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex humps according to claim 1, characterized in that: In step five, the speed of the press head is 10 mm / min.

7. The method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex humps according to claim 3, characterized in that: In step 5, after the sample is pressed into a convex shape, the diameter of the convex shape is ≤24 mm.

8. The method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex humps according to claim 1, characterized in that: In step six, the measurement accuracy of the protrusion height must reach 0.1mm.

9. The method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex hulls according to claim 7, characterized in that: The ratio of the diameter of the convex bulge after the sample is pressed into a convex bulge to the diameter of the sample is ≤0.

35.

10. The method for detecting hydrogen embrittlement performance of hydrogen embrittlement insensitive materials by pressing convex humps according to claim 1, characterized in that: In step 1, the number of samples is 6; in step 7, each sample is measured three times and the average value is taken.